Legal Reform the Meaning of Final and Binding Decisions of the Consumer Dispute Resolution Agency (Review of the Consumer Protection Act and Supreme Court Cassation Decision) - Nayila Rehman; M. Hamidi Masykur; Setiawan Wicaksono (Journal of Law and Legal Reform, 2024)
Consumer disputes in Indonesia can be resolved outside the court system through the Consumer Dispute Settlement Agency (BPSK), which issues decisions considered final and binding. Despite this, the legal framework permits objections to these decisions at the District Court, and further appeals to the Supreme Court, leading to considerable legal uncertainty. This research seeks to clarify the true nature of final and binding as applied to BPSK decisions under Article 54(3) of Law 8/1999. Utilizing a normative juridical approach with both statute and case law analysis, the study highlights a critical inconsistency: the finality of BPSK decisions does not align with the finality of Constitutional Court decisions. While regulations such as Kepmen 350/2001 and Perma 1/2006 were introduced to address these issues, BPSK still encounters practical difficulties in implementing Law 8/1999 effectively. The urgency of this research is underscored by the ongoing legal ambiguity surrounding BPSK decisions, which undermines public confidence and the effectiveness of the dispute resolution process. The findings reveal that despite regulatory attempts, the current legal framework fails to provide the necessary clarity and consistency. To address these challenges and enhance legal certainty for the public, this study advocates for a revision of the Consumer Protection Act (UUPK). Such a revision would ensure a more coherent and reliable framework for final and binding decisions by BPSK, thereby improving the overall efficacy of consumer dispute resolution in Indonesia.